Effectiveness of Specific Gravity Separation and Packaging Material in Enhancing the Planting Value of Onion (Allium cepa L.) Seeds - SWARAN LATA; J.K. SHARMA (Seed Research, 2026)
Onion (Allium cepa L.) seed crop (variety Patna Red) was raised in two consecutive years during 2002 and 2003 winter season and the seeds so recovered during summer 2003 and 2004, respectively, were first subjected to screen cleaner-cum-grader and further to specific gravity separator. The seeds so obtained were assessed for seed quality parameters immediately after processing. Thereafter, these were stored in high density polyethylene (HDPE) and cloth bag packaging up to next planting season. The seed quality parameters were also assessed before next planting season. Though screen processed seeds show superiority in the performance of all the seed quality parameters over the unprocessed seeds, yet specific gravity separation showed significant improvement in quality parameters over the performance of screen-processed seeds. Only 6 per cent reduction in seed recovery was observed after specific gravity separation in both the years, but the germination improved by 7 to 10 per cent, physical purity by 3 to 5 per cent, field emergence by 10 to 12 per cent, test weight by 0.08g to 0.06g and vigor index by 221 to 294, in two years of study, respectively. Further the HDPE packaging of these seeds maintained their quality parameters for a period of about 6 months by exhibiting only 3 to 4 per cent loss in germination and field emergence over the fresh initial seed, otherwise, which declined to 32-40 per cent in cloth bag packaging.